Art History and Fetishism Abroad: Global Shiftings in Media and Methods - Stercken, Angela; Genge, Gabriele (transcript, 2014)
By focusing on the various modes and media of the fetishised object, this anthology shifts the debates on thingness into a new global art historical perspective. The contributors explore the attention given to those material images, in both artistic and cultural practice from the heyday of colonial expansion until today. They show that in becoming vehicles and agents of transculturality, so called »fetishes« take shape in the 17th to 19th century aesthetics, psychology and ethnography – and furthermore inspire a recent discourse on magical practice and its secular meanings requiring altered art historical approaches and methods.